Analisis Penyebab Temper Tantrum pada Anak Usia Dini di PAUDQU Nurul Huda - Syaripah Aliyah; Sinka Nurussalam; Sri Wahyuni; Aneu Siti Rohmah (Edu Happiness : Jurnal Ilmiah Perkembangan Anak Usia Dini, 2024)
This study aims to analyze the causes of temper tantrums in early childhood. The method in this study is a descriptive qualitative method. Data collection techniques are carried out through observation techniques, interviews and documentation studies. The results of the study found that the cause of temper tantrums in early childhood at PAUDQU Nurul Huda Cintakarya is that children who are spoiled will make children able to take advantage of their parents. When children are often spoiled by parents and other family members, children will understand that everything they want will be followed and children will think they will not accept rejection from their parents. These habits that have been instilled by parents in children will make children become individualists and make children unable to get used to an environment that has a variety of attitudes.